2020
DOI: 10.1038/s41419-020-2662-2
|View full text |Cite
|
Sign up to set email alerts
|

POU4F1 promotes the resistance of melanoma to BRAF inhibitors through MEK/ERK pathway activation and MITF up-regulation

Abstract: BRAF inhibitors (BRAFi) have shown remarkable clinical efficacy in the treatment of melanoma with BRAF mutation. Nevertheless, most patients end up with the development of BRAFi resistance, which strongly limits the clinical application of these agents. POU4F1 is a stem cell-associated transcriptional factor that is highly expressed in melanoma cells and contributes to BRAF-activated malignant transformation. However, whether POU4F1 contributes to the resistance of melanoma to BRAFi remains poorly understood. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 46 publications
2
14
0
Order By: Relevance
“…Overexpression of the transcription factor POU4F1 (POU Class 4 Homeobox 1) contributed to the resistance to BRAFi in vemurafenib-treated melanoma cells by increasing MEK expression and activating MEK/ERK signaling. POU4F1 also increased the expression of MITF, further supporting resistance [ 54 ].…”
Section: Resistance To Inhibitors Of Mutated Braf In Melanomamentioning
confidence: 99%
“…Overexpression of the transcription factor POU4F1 (POU Class 4 Homeobox 1) contributed to the resistance to BRAFi in vemurafenib-treated melanoma cells by increasing MEK expression and activating MEK/ERK signaling. POU4F1 also increased the expression of MITF, further supporting resistance [ 54 ].…”
Section: Resistance To Inhibitors Of Mutated Braf In Melanomamentioning
confidence: 99%
“…As a well-documented example, transcription factors and coactivators play an active role in resistance to BRAF V600E targeted therapy, through a large variety of mechanisms [17]. In addition to promoting adaptive or acquired resistance, the expression levels of some of these transcription factors promotes a state of intrinsic resistance in the context of melanoma cells harboring BRAF V600E mutations [18][19][20].…”
Section: Therapeutic Resistance To Targeted Therapymentioning
confidence: 99%
“…Clinically, orally administrated trametinib (2 mg daily) However, clinical approval of orally administrated vemurafenib (FDA-approved, 2011: 960 mg twice daily) and dabrafenib (FDA-approved, 2013: 150 mg twice daily) was achieved based on their abilities to significantly improve both overall survival (13.6 and 20 months) and progression-free survival (5.3 and 6.9 months) in BRAF V600E -treated metastatic melanoma patients when compared to DTIC treated control offering poorer overall (9.7 and 15.6 months) and progression-free survival (1.6 and 2.7 months), respectively [6]. Nevertheless, the clinical benefits of the aforementioned targeted therapies were short-lived due to the development of resistance [6,22,23,50]. Recently, Erdmann et al (2020) have shown that prolonged exposure (12 months) of BRAF V600E -positive human-derived melanoma cells to vemurafenib simultaneously desensitized them to both vemurafenib and DTIC treatments [22].…”
Section: Summary Of Fda-approved Melanoma Chemotherapy and Targeted Therapiesmentioning
confidence: 99%
“…Thus far, two targeted therapeutic approaches have been developed using antagonist monoclonal antibodies (mAbs) or small molecules such as vemurafenib (FDA-approved, 2011), dabrafenib (FDA-approved, 2013), trametinib (FDA-approved, 2013), encorafenib, and binimetinib (FDA-approved, 2018) to obstruct agonistic ligand binding to cognate overexpressed tumor-associated antigen receptors (TAAs) or by inhibiting the oncogenic BRAF/MAPK/MEK (MEK: mitogen-activated protein kinase kinase) (originally known as extracellular signal-regulated kinases)-signaling axis [ 6 , 16 , 17 , 18 ]. However, the compromised efficacy of vemurafenib and other BRAF/MEK inhibitors have been associated with aberrant expression of membrane proteins known as ATP-binding cassette (ABC) transporters (e.g., ABCB5 and ABCG2), mediating cellular resistance by extruding cytotoxic molecules out from cells, as well as the re-activation of the MAPK pathway and to a lesser extent phosphatidylinositol-3 kinase (PI3K)–protein kinase-B (Akt) pathway activation and phosphatase and tensin homolog (PTEN) loss following prolonged targeted therapy treatments [ 6 , 19 , 20 , 21 , 22 , 23 ]. In contrast to BRAF inhibitors, mAbs partly exert their cytotoxic effects by reducing ectodomain density or by inducing receptor-mediated endocytosis through the activation of antibody-dependent cellular cytotoxicity (ADCC) toward tumor cells overexpressing the specific TAA [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation